A Case of Fecaloma Treated Medically - Igarashi, K.; Masamune, O.; Chiba, M.; Ohta, H.; Arakawa, H.; Horie, Y. (Nippon Daicho Komonbyo Gakkai Zasshi, 1987)
A 44-year-old woman was admitted to our department with a chief complaint of incomplete defecation. She had often been constipated after her first delivery and had used commercially available cathartics or enemas. She experienced a sensation of incomplete defecation associated with abdominal discomfort in the middle of September, 1985. These symptoms were gradually aggravated and were followed by urinary retention. She was treated for about a month by a doctor without relief of the symptoms and was referred to our department on November 13, 1985. Barium enema and sigmoidoscopy revealed a large solid stool mass at the rectosigmoid junction. Diagnosis of fecaloma was made. The fecaloma was expelled after dioctyl sodium sulfosuccinate. casanthranol (Bulkosol) (p.o.) and carboxymethylcellulose sodium (Bulkose) (enema) had been given for eight days. Only eight cases of large bowel fecaloma have been reported during the past thirty years in Japan. No cases have been reported in which the fecaloma was removed by drugs as in our case. Medical treatment with Bulkosol and Bulkose should therefore be tried in patients with large bowel fecaloma who are not complicated by ileus.